Murowany dwór na kopcu w Białaczowie koło Opoczna w świetle badań terenowych z lat 1997-1998 - Ziółkowska, Gabriela (Acta Universitatis Lodziensis. Folia Archaeologica, 2004)
The following article presents the results of excavations undertaken within a masonry manor house (site 3) in Białaczów in 1997-1998 and an analysis of material gained during the works. Białaczów is situated in the southeastern part of the Łódź voivodeship, about 10 km to the south of Opoczno. The village is known from written sources dated to the 1st half of the 13th century. In the Middle Ages it belonged to the Odrowąż family, in the 16th century as a result of relationships by marriage it got to the Kochanowski family. In the 1st half of the 18th century Białaczów was bought by the Małachowskis. The site under consideration lies within a park complex connected with the Małachowskis residence from the 18th century. It is an earthen mould on the plan of an oval, surrounded by partly irrigated moat. In the central part of the upper plateau there are relics of a masonry building forming a course of rooms (12 x 22 m) with complementary rectangular annex from the north-west. During archaeological excavations carried out in 1997 two ditches and three opencasts on total area of 31,75 sq m. In 1998 archaeological supervision connected with preserving the relics of the masonry manor house from further devastation was conducted. As a result of the archaeological research function of the discussed object as well as its preliminary chronology have been established.